Regulatory T Cells Promote Macrophage Efferocytosis during Inflammation Resolution - SÖZEN, AHMET ERDİ (CELL PRESS, 2018)
Regulatory T (Treg) cell responses and apoptotic cell clearance (efferocytosis) represent critical arms of the inflammation resolution response. We sought to determine whether these processes might be linked through Treg-cell-mediated enhancement of efferocytosis. In zymosan-induced peritonitis and lipopolysaccharide-induced lung injury, Treg cells increased early in resolution, and Treg cell depletion decreased efferocytosis. In advanced atherosclerosis, where defective efferocytosis drives disease progression, Treg cell expansion improved efferocytosis. Mechanistic studies revealed the following sequence: (1) Treg cells secreted interleukin-13 (IL-13), which stimulated IL-10 production in macrophages; (2) autocrine-paracrine signaling by IL-10 induced Vav1 in macrophages; and (3) Vav1 activated Rac1 to promote apoptotic cell engulfment. In summary, Treg cells promote macrophage efferocytosis during inflammation resolution via a transcellular signaling pathway that enhances apoptotic cell internalization. These findings suggest an expanded role of Treg cells in inflammation resolution and provide a mechanistic basis for Treg-cell-enhancement strategies for non-resolving inflammatory diseases.
Keywords: APOPTOTIC CELLS; ATHEROSCLEROSIS; PHAGOCYTOSIS; RECEPTOR; INTERLEUKIN-10; MECHANISMS; SUPPRESSION; NEUTROPHILS; LYMPHOCYTE; ACTIVATION